Decreased Serum 25-(OH)-D Level Associated With Muscle Enzyme and Myositis Specific Autoantibodies in Patients With Idiopathic Inflammatory Myopathy - Yu, Zhen; Cheng, Hao; Liang, Yuying; Ding, Tingting; Yan, Chenglan; Gao, Chong; Wen, Hongyan (Frontiers in Immunology, 2021)
Objectives: To determine whether there is serum vitamin D deficiency and the low levels of serum vitamin D are correlated with serological and immunological indexes in patients with idiopathic inflammatory myopathy (IIM). Methods: A total of 63 newly diagnosed patients with IIM, and 55 age- and sex- matched healthy controls were enrolled. Serum levels of 25-(OH)-D were measured by enzyme-linked immunosorbent assay. The correlations of 25-(OH)-D levels with disease indicators and T cell subsets were analyzed. Result: The levels of serum 25-(OH)-D in IIM were significantly lower than those in healthy controls (9.36 ± 5.56 vs 26.56 ± 5.37 ng/ml, p<0.001). The levels of serum liver enzyme ALT and AST and muscle enzyme CK, CKMB, LDH and HBDH were elevated as deficiency of vitamin D. In addition, the serum 25-(OH)-D levels were negatively correlated to ALT (r = -0.408, p = 0.001) and AST (r = -0.338, p = 0.007). The 25-(OH)-D levels in IIM patients in presence of anti-Jo-1 were significantly lower than those in patients without anti-Jo-1 (5.24 ± 3.17 vs 9.32 ± 5.60 ng/ml; p = 0.037). Similar results were found in patients with or without anti-Mi-2 antibody. The serum 25-(OH)-D levels were positively associated with total T (r = 0.203, p = 0.012) and Treg cells (r = 0.331, p = 0.013). The patients with deficient levels of vitamin D were more likely to have heliotrope, gastrointestinal and liver involvement. Conclusions: Vitamin D deficiency existed in IIM patients, which was significantly correlated with muscle enzyme, presence of anti-Jo-1 and anti-Mi-2 antibody, and the absolute numbers of total T and Treg cells in IIM. It is suggested that vitamin D may play an important role in the immunological pathogenesis of IIM.